Economic burden associated with adverse events of special interest in patients with relapsed Philadelphia chromosome-negative B-cell acute lymphoblastic leukemia in the United States. (3rd September 2018) - Zhang, Xinke; Song, Xue; Lopez-Gonzalez, Lorena; Jariwala-Parikh, Krutika; Cong, Ze
ABSTRACT: Background : Infections, cytopenia, and gastrointestinal (GI) toxicity are adverse events of special interest (AESI) affecting most relapsed Philadelphia chromosome–negative (Ph−) B-cell acute lymphocytic leukemia (ALL) patients. This study quantified real-world rates and economic burden of these events among relapsed Ph− B-cell ALL patients in the United States. Methods : Adults with relapsed Ph− B-cell ALL during 1 April 2009–31 October 2016 were selected from MarketScan® healthcare claims databases. Outcomes included proportions of patients with AESIs and AESI-related costs during 100 days after relapsed hospitalization. Results : Of 400 relapsed Ph− B-cell ALL patients, 92.5% experienced ≥1 AESI during the median 100-day follow-up, of which 64.6% had infections, 94.6% cytopenia, and 46.2% GI toxicities. Mean (SD; median) AESI-related total cost per patient during follow-up was 197, 213 (308, 551; 105, 731), with a mean of 2 AESI-related hospitalizations comprising 32.2 inpatient days. Mean (SD; median) healthcare costs were highest for infections (164, 461 [347, 083; 64, 528]), followed by cytopenia (125, 210 [165, 141; 67, 475]) and GI events (11, 652 [40, 231; 1349]). Conclusion : The economic burden of AESIs is substantial, with infections the most expensive, followed by cytopenia and GI toxicity. New therapies that can improve outcomes in relapsed Ph− B-cell ALL while offering a favorable safety profile are needed.